Morphological and molecular characteristics of Panax sp. (Araliaceae) from Phu Xai lai leng mountain, Nghe An province, Vietnam - Long, Phan Ke; Viet Thanh, Tran Thi; Tao, Nguyen Thien; Loc, Phan Ke; Lenh, Nguyen Tu; Lam, Nguyen Tien; Minh, Dang Xuan (Academia Journal of Biology, 2015)
Seven sterile and young specimens of Panax sp. were collected in Phu Xai Lai Leng silicat mountain, the highest mountain  peak in central Vietnam. Morphologically, they resemble P. stipuleanatus and P. bipinnatifidus. However, they have stipules and leaflets that are not bipinnatifid. The ITS-DNA sequences of Panax sp. from Phu Xai Lai Leng are identical and exhibit a close relationship with P. stipuleanatus from Tam Duong district, Lai Chau province with strong bootstrap support (98%). Noticeably, these two taxa  are different by 2 nucleotides. A collection of standard specimens including inflorescence, infructescence, flowers and ripe fruits of Panax from Phu Xai Lai Leng is needed to determine its taxonomic status.